The Development of Practice Standards for Radiation Oncology in Australia: A Tripartite Approach. Issue 6 (June 2015) - Kron, T.; Dwyer, M.; Smith, L.; MacDonald, A.; Pawsey, M.; Raik, E.; Arnold, A.; Hill, B.; Duchesne, G.M.
Abstract In many areas of health care, practice standards have become an accepted method for professions to assess and improve the quality of care delivery. The aim of this work is to present the development of practice standards for radiation oncology in Australia, highlighting critical points and lessons learned. Following a review of radiotherapy services in Australia, a multidisciplinary group with support from the Australian Government developed practice standards for radiation oncology in Australia. The standards were produced in a multistep process including a nationwide survey of radiotherapy centres and piloting of the standards in a representative subset of all Australian radiotherapy centres. The standards are grouped into three sections: Facility management (covering staffing, data management, equipment and processes); Treatment planning and delivery (providing more detailed guidance on prescription, planning and delivery); Safety and quality management (including radiation safety, incident monitoring and clinical trials participation). Each of the 16 standards contains specific criteria, a commentary and suggestions for the evidence required to demonstrate compliance. The development of the standards was challenging and time consuming, but the collaborative efforts of the professions resulted in standards applicable throughout Australia and possibly further afield.